Supply Chain Challenges Faced by Auto-Component Manufacturers in India - Aggarwal, Rohan (2012)
The paper analyses the various problems the auto component manufacturing industries in India face in their supply chains. It studies the some of the best practices for a successful supply chain suggested by the existing literature and their relevance to the component manufacturing industries in India. The objective of the research is to understand the problems which these manufacturers face and form recommendations for their survival in the competitive world. The literature review describes the various theories and practices suggested by experts and scholars. For this purpose of research, qualitative research methodology has been chosen. The researcher has taken interviews in order to understand and satisfy the aims and objectives of this research. The results from the interviews have been discussed and analyzed by dividing them into various themes based on the literature review. Lastly, the concluding thoughts of this study discuss the limitations and recommendations.